Then peut-il vraiment introduire un repérage temporel ? - Michaël Vallée (Corela, 2005)
The connective then has not received much attention so far. In this paper, I only focus on the temporal use of then that can mainly be found in a succession of events. I try to show that the label of temporal adverb is not easy to demonstrate in this type of sequence. After examining the observations of some linguists about the subject, I suggest that it is possible to have a different viewpoint on the function of then with a temporal interpretation.